Comparative performance evaluation of different HPV tests and triaging strategies using self‐samples and feasibility assessment of thermal ablation in 'colposcopy and treat' approach: A population‐based study in rural China. Issue 5 (8th February 2020) - Zhao, Xue‐Lian; Xu, Xiao‐Qian; Duan, Xian‐Zhi; Rezhake, Remila; Hu, Shang‐Ying; Wang, Yan; Xia, Chang‐Fa; Zhang, Xun; Qiao, You‐Lin; Sankaranarayanan, Rengaswamy; Zhao, Fang‐Hui; Basu, Partha
Abstract : Human papillomavirus (HPV) test, self‐sampling and thermal ablation for cervical intraepithelial neoplasia (CIN) have been developed separately to increase screening coverage and treatment compliance of cervical cancer screening programmes. A large‐scale study in rural China screened 9, 526 women with their combinations to explore the optimal cervical cancer‐screening cascade in the real‐world. Participants received care HPV and polymerase chain reaction (PCR) HPV tests on self‐collected samples. Women positive on either HPV test underwent colposcopy, biopsy and thermal ablation in a single visit. Samples positive on either HPV test were retested for genotyping. Absolute and relative performance of HPV tests, triage strategies, 'colposcopy and thermal ablation' approach were statistically evaluated. PCR HPV test detected 33.3% more CIN grade two or worse (CIN2+) at a cost of 28.1% more colposcopies compared to care HPV. Sensitivities of PCR HPV and care HPV tests to detect CIN2+ were 96.7 and 72.5%. Specificities for the same disease outcome were 82.1 and 86.0%. Triaging HPV‐positive women with HPV16/18 genotyping considerably improved the positive predictive value for CIN2+ (4.8–5.0 to 18.2–19.2%). Ninety‐six women positive on HPV and having abnormal colposcopy were eligible for thermal ablation and all accepted same‐day treatment, contributing to 64.6% being treated appropriately (CIN1+ on histopathology), which reached up to 84.8% among women positive on HPV 16/18 triage. No serious side‐effects/complications were reported. The combination of PCR HPV test followed by HPV 16/18 triaging on self‐collected samples and colposcopy of triage positive women followed by immediate thermal ablation might be the appropriate screening cascade for rural China. Abstract : What's new? To be effective, cervical cancer screening programs must be tailored to the needs of the target population. In rural China, screening coverage is low, and women may not return for separate diagnosis and treatment visits. Here, the authors evaluated various screening protocols under real world conditions. They found that self‐sampling, PCR HPV test and triage based on HPV16/18 genotyping, followed by colposcopy and immediate thermal ablation in a single visit, could be the most efficient screening cascade for this rural population. This plan reduced costs while increasing compliance for follow up care.